GI Assisted Go: An Innovative Learning Model to Improve Students Creative Thinking Ability - Irawati, E; Ismaniati, C (KnE Social Sciences, 2019)
The purpose of this research is to improve students’ creative thinking ability through Group Investigation (GI) learning model assisted by Graphic Organizer (GO) in science education subject by using classroom action research. The subjects of the study were class II/E PGSD, FIP, UNY students. Data collection techniques used observation and test. Data analysis techniques used quantitative descriptive and n-gain. Indicators of creative thinking ability include fluency, originality, flexibility, and elaboration. The results of this study indicate the implementation of GI assisted GO, in Cycle I, the implementation reached 81.25% with good category, increased up to 97.90% in cycle II with very good criteria. The result of creative thinking ability test in Cycle I reached 69.95 with creative category, up on Cycle II to 80.35 with creative category. In addition, the improvement of students’ creative thinking ability before and after action is also increasing, the normalized gain test result between Pre-cycle and Cycle I is 0.20 with low category, whereas between Pre-cycle and Cycle II it increases to 0.48 with category medium. The conclusion of this research indicates that the implementation of GI assisted GO can improve students’ creative thinking ability in the process of learning activity of science education course. The purpose of this research is to improve students’ creative thinking ability through Group Investigation (GI) learning model assisted by Graphic Organizer (GO) in science education subject by using the classroom action research. The subjects of the study were class II/E PGSD, FIP, UNY students. Data were collected from observation and test. Data analysis techniques used quantitative descriptive and n-gain. Indicators of creative thinking ability include fluency, originality, flexibility, and elaboration. The results of this study indicate the implementation of GI assisted GO, in cycle I implementation reached 81.25% with good category, increased up to 97.90% in cycle II with very good criteria. The result of creative thinking ability test in cycle I reached 69.95 with creative category, up on cycle II to 80.35 with creative category. In addition, the improvement of students’ creative thinking ability before and after action is also increasing, the normalized gain test result between pre-cycle and cycle I is 0.20 with low category, whereas between pre-cycle and cycle II it increases to 0.48 with category medium. The research concludes that the implementation of GI assisted GO can improve students’ creative thinking ability in the process of learning activity of science education course. Keywords: creative thinking ability, group investigation (GI) learning model assisted graphic organizer (GO)